All-Trans-Retinoic-Acid Unmasking Hypercalcemia of Hyperparathyroidism - Yanamandra, Uday (Indian J Hematol Blood Transfus, 2015)
We present a patient of acute promyelocytic leukaemia managed with all-trans-retinoic-acid and arsenic trioxide who developed hypercalcemia with target organ damage. The patient also was simultaneously discovered to be symptomatic from hyperparathyroidism, which was unmasked after ATRA administration. Patient was successfully managed without any interruption of ATRA therapy and parathyroidectomy. We discuss the mechanisms of ATRA in causing hypercalcemia and its possible role in index case in unmasking hyperparathyroidism. Present case refutes Occam’s razor and emphasise that known adverse effects shouldn’t withhold clinicians from working up for other common causes for a given condition.